Alloying effects on the microstructure and mechanical properties of nanocrystalline Ti-based alloyed thin films. Issue 39 (30th September 2021) - Hou, Zhaoqi; Zhang, Jinyu; Zhang, Peng; Wu, Kai; Wang, Yaqiang; Liu, Gang; Zhang, Guojun; Sun, Jun
Abstract : The plastic deformation of nanocrystalline Ti alloyed films is mainly mediated by the partial dislocation mechanism emanating from grain boundaries. Abstract : Ti-based films alloyed with various Ta or Zr contents were deposited on a Si (100) substrate by magnetron sputtering. Transmission electron microscopy observations suggested that the solute Ta and Zr atoms distributed uniformly in the matrix Ti, refining the grain size. The microstructure transformed from single phase α-Ti to the coexistence of (α + β)-Ti when the Ta addition was increased to 18.2 at%. Hardness and strain rate sensitivity of the Ti-based alloyed films were evaluated by nanoindentation experiments, to show the effects of constituents and their contents. The hardness was found to change non-monotonously within the studied Ta or Zr range, which could be explained by alloying dependence of the strengthening mechanisms, including partial dislocation mechanism emanating from grain boundaries, solid solution strengthening, and solution pinning strengthening. Furthermore, a mechanistic model based on partial dislocation inhomogeneous nucleation was employed to describe the composition-dependent strain rate sensitivity of the alloyed Ti films.